PENERAPAN METODE QUALITY FUNCTION DEPLOYMENT (QFD) DALAM PERANCANGAN DAN PEMBUATAN ALAT PEMANENAN KELAPA SAWIT BERMOTOR PADA DI INDUSTRI KELAPA SAWIT : PERANCANGAN DAN PEMBUATAN ALAT PEMANENAN KELAPA SAWIT BERMOTOR - Reky Kurnia Widhi, Andreas; Nugroho, Oktavianus Ardhian; Kumbarasari, Shanti (Infotekmesin, 2025)
In the oil palm plantation industry, several motorized palm oil harvesting equipment already exist in the palm oil industry market. Several motorized palm harvesting equipment, such as STIHL PC 70 and Tanika TS-5, are on the market. These two machines are rarely used because the tool's price is still high compared to the manual method. One part that makes both tools expensive is the gearbox. In addition, this part is the most often damaged so it requires a long repair time and increases the time to harvest oil palm. This research aims to design a gearbox for oil palm harvesting equipment that is low-cost, lightweight, and tough. The Quality Function Deployment (QFD) method was chosen to prototype the palm oil harvesting gearbox. The results of this research obtained a prototype gearbox that is lightweight and has a tough mechanical system. In addition to its manufacture, which is carried out independently and using local materials, the production cost of the gearbox is low, even when it is still in prototype form.